PENGARUH PROMOSI MEDIA SOSIAL DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SOSMED CAFE ABDULLAH LUBIS MEDAN - Barus, Clara Silvina; Silalahi, Donalson (UNIKA Santo Thomas, 2021)
Abstract This study aims to determine and explain the effect of social media promotion and service quality on purchasing decisions. To achieve this goal, research was conducted at Social Media CafÃ© Abdullah Lubis using 100 people as respondents. Data were collected through questionnaires and the analysis technique used was multiple linear regression analysis. The results showed: First, social media promotion has a positive and significant effect on purchasing decisions. Second, service quality has a positive and significant effect on purchasing decisions. Third, service quality plays a greater role in increasing the sensitivity of consumer purchases when compared to social media promotion. Fourth, consumer characteristics are also important variables in increasing consumer decisions in buying products. Fifth, social media promotion and service quality are able to explain variations in purchasing decisions by 87.7 percent.